Preparation method of antique pigment

Through the preparation method of antique pigments, the problems of scarcity and unstable color difference of traditional mineral pigments are solved. The resulting pigments have uniform particles, ultraviolet light resistance and high toughness coating, which are suitable for the production and protection of traditional painting works.

CN119192880APending Publication Date: 2024-12-27JOINT SUCCESS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410551639.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-06
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional mineral pigments have become scarce resources, and due to personal preferences and technical differences, it is difficult to mass produce, and there are problems such as unstable batch color difference, complex process and long cycles.

Method used

Using a preparation method of antique pigment, the ore base material and connecting material are formed through ore pretreatment and antique pigment preparation steps, including ore preliminary screening, crushing, magnetic field treatment, pickling, drying, aging, etc., to form ore base material and connecting material, combined with colloids, Components such as honey, fillers, rosin, etc., the antique pigment produced has uniform particles, ultraviolet light resistance, non-discoloration and high toughness coating.

Benefits of technology

The antique pigments have uniform particle size, uniform dispersion, excellent UV resistance, no discoloration and high film formation, meet the needs of traditional hand-painted or spraying, and the coating is resistant to friction and fading, which is suitable for the protection of traditional paintings and Production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192880A_ABST
    Figure CN119192880A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of pigments, and relates to a preparation method of an antique pigment, which comprises the following steps: pretreating ores, drying centrifuged supernate to form an ore base material 1, drying solid sediments, oxidizing with mixed acid to form an ore base material 2, and drying; and adding the ore base material 1 into a binder, uniformly dispersing, adding colloid, honey, filler and rosin, uniformly dispersing again, placing in a shady, cool and dry environment, aging for 1-5 years, and removing a deteriorated area to obtain the ore base material grafted polyurethane composite material. The ore base material grafted polyurethane disclosed by the invention contains rich long chain segments, and has good wrapping performance on other micromolecular components, so that a final pigment coating is relatively good in film-forming property, toughness, oily feeling and the like, is resistant to friction, is not obvious in fading phenomenon or negligible in fading, is not easy to crack, and is friendly in later maintenance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pigments, relates to antique pigments, and in particular to a preparation method of antique pigments. Background Art

[0002] Chinese painting has a long and glorious history. For thousands of years, numerous painters have devoted their efforts to creating works, passing on the tradition from generation to generation, and have formed an independent form of expression and artistic style. The experience passed down is rich and colorful, and the system is complex. When inheriting the national painting heritage, the understanding of the characteristics of material materials and techniques cannot be ignored.

[0003] Nowadays, people can still see many colorful ancient paintings, the earliest of which can be traced back to 2,000 years ago, and the latest one is more than 800 years old, but the colors in the paintings still maintain a good degree of brightness, and even have various tones and atmospheres. There are documents that more than 1,400 years ago, the painter Xie He proposed the theory of "coloring according to the type" in his "Six Laws Theory"; more than 1,100 years ago, art critic Zhang Yanyuan described the origin, use and reasons for the unchanged painting pigments at that time in his "Records of Famous Paintings of All Dynasties". Later, in various eras, many painters have more or less summed up the methods of using pigments through practice, and these experiences are of great value to the study of color theory in Chinese painting.

[0004] The existence and application of mineral pigments make Chinese heavy-color paintings strongly exude the unique charm of oriental paintings in the world of painting art, with a strong oriental mood and aesthetics. So far, there are more than 40 kinds of pure natural mineral colors and more than 30 kinds of high-temperature crystallization colors. Each color can be divided into more than eight models with different particle sizes and different shades of color, forming a relatively complete mineral color system. The performance of mineral pigments and their metal pigment auxiliary materials (such as various gold foils, gold mud, gold powder, etc.) more fully provides the possibility of using various techniques on a flat base. The production process is the artist's conscious and skillful selection and use of granular pigments and their auxiliary materials to express artistic ideas and form artistic images. The creation process. Chinese paintings using mineral colors have a strong painterly quality and visual impact, which not only expresses the ideological content given by the artist, but also shows the unique beauty of the material itself.

[0005] However, it is worth noting that mineral pigments in the traditional sense have now become a scarce resource, and mineral pigments produced by painters' personal preferences and differences in skills are difficult to mass-produce. In addition, traditional mineral pigments also have many problems such as unstable batch color difference, complex process, and lengthy cycle that need to be solved urgently. Summary of the invention

[0006] First of all, mineral pigments in the traditional sense have become a scarce resource, and the mineral pigments produced are difficult to mass-produce due to the personal preferences and craftsmanship differences of manufacturers. In addition, traditional mineral pigments also have many problems such as unstable batch color difference, complex process, and lengthy cycle. The purpose of the present invention is to disclose a method for preparing antique pigments.

[0007] Technical Solution

[0008] A method for preparing an antique pigment comprises the following steps:

[0009] (1) Ore pretreatment:

[0010] The ore raw material is crushed after primary screening, and a soluble alkaline salt is added to stir evenly and piled in an open-air natural environment for 4 to 50 months, preferably 24 months; the piled ore raw material is crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 300 to 760 mT, preferably 455 mT, to adsorb and remove impurities; the ore powder is washed with a dilute acid solution for 2 to 9 times, preferably 5 times, and then washed with water to a pH of 5.6 to 7.1, preferably pH 6.8 after draining; then water is used to prepare a suspension, and centrifuged to separate the solid and liquid; the supernatant is dried to form an ore base material 1, and the solid sediment is dried and oxidized with a mixed acid to form an ore base material 2, which is dried for standby use;

[0011] The so-called initial screening is to use the naked eye as the basis for judgment. Its purpose is to pick out the base material with the best color and purity from the ore raw materials, so as to facilitate the subsequent removal of impurities and support the subsequent preparation of antique pigments with pure colors; the purpose of adding soluble alkaline salts is to form coordination crystals with impurities in the ore raw materials during long-term stacking, so as to facilitate the removal of impurities during subsequent acid washing and water-based treatment. The addition of soluble alkaline salts can inhibit the growth of microorganisms and prevent mildew; stacking in an open-air natural environment is to weather and mature the ore raw materials to form a loose structure for subsequent processing;

[0012] The ore is lapis lazuli, lapis lazuli, dianqingshi, dianqingshi, malachite, cinnabar, cinnabarite, orpiment, realgar, orpiment, ochre, ochre, bean green, male essence, qingqing, qingqing, shaqingshi, chalk or black ochre. Different types of ore can be used to obtain ore base materials 1 and ore base materials 2 with different colors and tones, and finally obtain antique pigments with corresponding hues; the soluble alkaline salt is sodium carbonate, potassium sulfite, sodium bicarbonate, potassium sulfate, sodium hypochlorite, sodium thiosulfate or trisodium phosphate, preferably sodium thiosulfate; the dilute acid is 0.02-0.5mmol / L hydrochloric acid, nitric acid or sulfuric acid, preferably 0.08mmol / L hydrochloric acid; the mixed acid is concentrated sulfuric acid, concentrated nitric acid, perchloric acid, concentrated hydrochloric acid, hydrobromic acid, hydroiodic acid, perbromic acid, hydroiodic acid , fluorosilicic acid, chlorolead acid, metaphosphoric acid, osmic acid, permanganic acid, selenic acid, ferric acid, fluoroboric acid, fluorosulfonic acid, cyanic acid, thiocyanic acid, 2,4,6-trinitrophenol, 2,4,6-trinitrobenzoic acid, trifluoroacetic acid, trichloroacetic acid, methanesulfonic acid, benzenesulfonic acid, KMD acid, oxalic acid, 2-chloroethanethiol, fluoroantimonysulfonic acid, perfluorosulfonic acid resin, carborane acid, Tribull volatile acid in any ratio, preferably a combination of concentrated sulfuric acid and permanganic acid, the mixing ratio is 5g:0.2g; the reaction material ratio of ore, soluble alkaline salt, water for preparing suspension, and mixed acid is 10.0g:0.5-2.3g:20-200mL:20-100mL, preferably 10.0g:0.7g:160mL:57mL;

[0013] (2) Preparation of antique pigments:

[0014] Add the above-mentioned ore base material 1 to the connecting material and disperse it evenly, add colloid, honey, filler and rosin and disperse it evenly again, place it in a cool and dry environment for aging for 1 to 5 years, preferably 3 years, remove the deteriorated area, and obtain; the colloid is animal colloid or plant colloid, wherein the animal colloid is tortoise shell glue, egg white, fish maw boiled extract, animal leather boiled extract or beeswax, and the plant colloid is agar, peach gum, sesbania gum, guar gum, sesame gum, fenugreek gum, eucommia gum or glutinous rice soup, preferably tortoise shell glue; the honey is rape honey, linden honey, vitex honey, loquat honey or sophora flower honey, preferably linden honey honey; the filler is 80-2000 mesh calcium bicarbonate powder, titanium dioxide powder, white carbon black powder, alumina powder, montmorillonite powder, pearl powder or shell powder, preferably 800 mesh titanium dioxide powder; the rosin is horsetail rosin, wetland rosin, Simao rosin, longleaf rosin, Cuban rosin or torch rosin, etc., preferably Simao rosin; the mass ratio of the reaction materials of ore base material 1, connecting material, colloid, honey, filler and rosin is 80:5-18:2-10:0.01-0.50:2-10:0.2-0.9, preferably 80:13:8:0.41:4:0.4;

[0015] The evenly dispersed materials are placed in a cool and dry environment for aging. The purpose is to warm and harmonize, reduce restlessness and heat, avoid the "thief light" reflected by the pigment after being colored on the surface of the object, and ensure that the pigment layer shows an ancient texture; the purpose of adding honey is to increase the oiliness and viscosity of the pigment, and play a certain anti-corrosion role in the subsequent aging stage.

[0016] The connecting material is prepared by the following method:

[0017] After fully dissolving polyisocyanate and polyol with solvent, add and heat to 60-210°C, preferably 182°C, add chain extender, catalyst 1 and ore base material 2 and keep warm for 2-17h, preferably 11h; adjust the system temperature to 41-115°C, preferably 92°C, add activator and catalyst 2, keep warm for 8-16h, preferably 9h; adjust the system temperature to 5-36°C, preferably 12°C, add passivator and keep warm for 5-45min, preferably 22min; adjust the system temperature to room temperature and remove most of the solvent to obtain ore base material grafted polyurethane, i.e. connecting material; the polyisocyanate is dimethyl diphenyl diisocyanate, diphenylmethane-4,4'-diisocyanate, terephthalate isocyanate, hexamethylene diisocyanate, 1,5-naphthalene diisocyanate, isophorone diisocyanate, 4,4-diisocyanate dicyclohexylmethane, o-phenylenediisocyanate or toluene-2,6-diisocyanate, preferably dimethylbiphenyl diisocyanate; the polyol is polybutadiene diol, polybutylene adipate (diol), polybutylene glycol, polycaprolactone (diol), polyethylene adipate (adipate) propylene glycol (adipate) ester (diol), polytetramethylene glycol, polyoxytetramethylene glycol, polytetrahydrofuran, polytetramethylene ether glycol, polypropylene glycol or polyoxypropylene glycol, preferably polybutylene adipate (diol); the solvent is ethyl acetate, dioxane, benzene, toluene, xylene or dimethylformamide, preferably dioxane; the chain extender is 1,4-butanediol, ethylene glycol, diethylene glycol, neopentyl glycol, glycerol, trimethylolpropane, 3,3'-dichloro-4,4'-diaminodiphenylmethane, 3,5-dimethylthiotoluenediamine, 3,5-diethyltoluenediamine, 2,4-diamino-3,5-dimethylthiochlorobenzene, isophoronediamine, ethanolamine, diethanolamine, triethanolamine or triisopropanolamine, N,N-bis(2-hydroxypropyl)aniline, preferably 1,4-butanediol; the catalyst 1 is dibutyltin dilaurate (DBTL), phenylmercuric acetate, phenylmercuric propionate, stannous octoate, potassium isooctanoate, potassium acetate, di(dodecylsulfide)dibutyltin, Tetramethylethylenediamine, tetramethylpropylenediamine, N-methylimidazole, N-methylmorpholine or 1,4-dimethylpiperazine, preferably dibutyltin dilaurate; the activator is thionyl chloride, oxalyl chloride, phosphorus trichloride, phosphorus oxychloride, diketene, phthalic anhydride, p-toluenesulfonyl isocyanate, methacrylic acid chloride, methacrylic anhydride, methacrylic acid, dicyclohexylcarbodiimide, N,N-diisopropylcarbodiimide, carbodiimide hydrochloride, 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate, O-benzotriazole-tetramethyluronium hexafluorophosphate or O-benzotriazole-N,N,N',N'-tetramethyluronium tetrafluoroborate, preferably oxalyl chloride;The catalyst 2 is 4-dimethylaminopyridine, 4-pyrrolidinylpyridine (4-PPy), N-hydroxysuccinimide, 1-hydroxybenzotriazole or 1-hydroxy-7-azabenzotriazole, preferably 4-pyrrolidinylpyridine; the passivating agent is ethylenediamine, n-propylamine, 1,3-propylenediamine, n-butylamine, 1-aminopentane, 3-aminoethylbenzene, 1-phenylpropan-1-amine, 4-methylphenylethylamine, 3,3-diphenylpropylamine, 3-methyl-1-phenylethylbutylamine, m-methylphenylethylamine or 1-naphthylmethylamine, preferably 4-methylphenylethylamine; polyisocyanate, polyol, solvent The reaction materials of the agent, chain extender, catalyst 1, ore base material 2, activator, catalyst 2, and passivator are 0.1mol: 0.08-0.25mol: 15-500mL: 0.1-12.8mmol: 0.01-0.93mg: 3-15g: 0.07-0.14mol: 0.2-15mg: 0.04-0.50mol, preferably 0.1mol: 0.17mol: 320mL: 11.2mmol: 0.66mg: 8g: 0.12mol: 10mg: 0.10mol. ;

[0018] Experimental methods

[0019] (1) Transmission electron microscopy (TEM)

[0020] About 0.2 g of sample was weighed and dispersed evenly with 50 mL of castor oil. A transmission electron microscope (JEM-2100F, Japan Co., Ltd.) was used to characterize the internal microstructure of the dispersed sample. The sample was fixed under the observation microscope, the observation size was adjusted to a clear state, and the internal structure and morphology of the sample at this size were recorded;

[0021] (2) Field emission scanning electron microscopy (SEM)

[0022] The antique pigments were applied to the canvas surface by traditional brush painting and spraying, and the microstructure of the pigment surface was characterized by a field emission scanning electron microscope (Hitachi S-4800, Japan Co., Ltd.). The sample was fixed under the observation microscope, and the observation size was adjusted to a clear state, and the surface structure and morphology of the pigment at this size were recorded.

[0023] (3) UV resistance

[0024] Take antique pigment and evenly apply it on the surface of white cardboard with a size of 10cm*10cm, with a coating thickness of about 0.5mm, and place it under vertical ultraviolet light for 24 hours, detect and record the coating color difference data before and after ultraviolet light irradiation, and set the main wavelength of the ultraviolet light source to 365nm, the power to 1200W, the ultraviolet radiation energy to 1700J / s, and the vertical distance of the light source to 15cm;

[0025] (4) Color difference detection

[0026] The color difference value of the surface coating of the sample obtained in (3) was tested by using a colorimeter (Ci7600, X-Rite, USA), and the parameters were recorded and the color difference value was calculated according to formula (1);

[0027] ΔE ab = [(ΔL) 2 +(Δa) 2 +(Δb) 2 ] 1 / 2 (1)

[0028] In the formula, ΔE ab ——Color difference of the sample before and after ultraviolet light irradiation, ΔL——Brightness change of the sample before and after ultraviolet light irradiation, Δa——Red and green color cast of the sample before and after ultraviolet light irradiation, Δb——Yellow and blue color cast of the sample before and after ultraviolet light irradiation;

[0029] (5) Friction fading test

[0030] The ink friction tester (2000 model, Sutherland, USA) was used to set the pressure at 4 pounds and the rotation speed at 85 minutes to test the color fading of the pigment layer of the sample obtained in (3) after the 1 minute friction test;

[0031] Traditional painting pigments commonly sold on the market are purchased as reference products. The reference products purchased for color difference test and friction fading resistance test should be as similar as possible to the color of the antique pigment prepared in the embodiment of the present invention.

[0032] Beneficial Effects

[0033] Mineral pigments in the traditional sense have become scarce resources, and mineral pigments obtained by manufacturers' personal preferences and differences in skills are difficult to mass-produce. In addition, traditional mineral pigments also have many problems such as unstable batch color difference, complex process, and lengthy cycle. The present invention discloses a method for preparing antique pigments, which comprises the following steps: preliminarily processing and separating ore raw materials to obtain ore base material 1 and ore base material 2, wherein the ore base material 1 is directly used as an antique pigment component, and the ore base material 2 is further modified by polyurethane grafting to obtain a connecting material as an antique pigment component, and the antique pigment is finally obtained by combining colloid, honey, filler, and rosin; the particle size of the obtained antique pigment is It is uniform, evenly dispersed, and not easy to settle, which can meet the requirements of traditional hand-painting or spraying, and the pigment coating has excellent UV resistance and is not easy to change color; the mineral base material grafted polyurethane disclosed in the present invention contains rich long-chain segments and has good wrapping properties for other small molecule components, so the final pigment coating has good film-forming properties, toughness, oiliness, etc., is resistant to friction and the discoloration phenomenon is not obvious or the discoloration is negligible, the coating is not easy to crack, and the maintenance of the coating in the later stage is also relatively friendly; it is worth mentioning that in the preparation stage of the antique pigment raw materials, they are ripened and aged many times to eliminate the "fire" of the pigment raw materials themselves, so that the surface of the final work is dignified and elegant without gleaming. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 .Process flow chart of the preparation method of antique pigment;

[0035] Figure 2 . TEM images of the obtained mineral-based grafted polyurethane linker dispersion, wherein (a) represents Example 1 and (b) represents Example 20;

[0036] Figure 3 SEM images of the pigment coatings obtained by the traditional brush painting and spraying of antique pigments, wherein (A) represents the traditional brush painting of Example 1 (B) represents the traditional brush painting of Example 20 (C) represents the spraying of Example 1 (D) represents the spraying of Example 20;

[0037] Figure 4 . Comparison chart of color fading due to friction, where (Ⅰ) represents the reference product and (Ⅱ) represents the antique pigment of Example 1. DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with specific embodiments, and the following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention.

[0039] Example 1

[0040] A preparation method of an antique pigment and its formula composition are as follows:

[0041] 10.0g of lapis lazuli ore raw material was crushed after primary screening, 0.7g of sodium thiosulfate was added, stirred evenly and piled in an open-air natural environment for 24 months; the piled ore raw material was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 455mT to adsorb and remove impurities; the ore powder was washed with 0.08mmol / L hydrochloric acid solution for 5 times, drained and washed with deionized water to pH 6.8; 160mL of deionized water was then used to prepare a suspension, and the suspension was centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 57mL of a mixture of concentrated sulfuric acid and permanganate (5g:0.2g) to form an ore base material 2, which was dried for standby use;

[0042] 80g of the above-mentioned ore base material 1 is added to 13g of the connecting material and dispersed evenly, 8g of tortoise shell glue, 0.41g of linden honey, 4g of 800 mesh titanium dioxide powder, and 0.4g of Simao rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 3 years, and the deteriorated area is manually removed to obtain;

[0043] The preparation method of the connecting material in the formula is as follows:

[0044] 0.1 mol of dimethylbiphenyl diisocyanate and 0.17 mol of polybutylene adipate (diol) were fully dissolved in 3200 mL of dioxane, and then the temperature was raised to 182°C, and 11.2 mmol of 1,4-butanediol, 0.66 mg of dibutyltin dilaurate and 8 g of ore base material 2 were added and kept warm for 11 hours; the system temperature was adjusted to 92°C, 0.12 mol of oxalyl chloride and 10 mg of 4-pyrrolidinopyridine were added, and the temperature was kept warm for 9 hours; the system temperature was adjusted to 12°C, 0.10 mol of 4-methylphenylethylamine was added, and the temperature was kept warm for 22 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore-based grafted polyurethane, i.e., connecting material.

[0045] The synthesis route of this embodiment is shown below:

[0046]

[0047] Example 2

[0048] A preparation method of an antique pigment and its formula composition are as follows:

[0049] 10.0g of lapis lazuli ore raw material was crushed after primary screening, 0.5g of sodium thiosulfate was added, stirred evenly and piled in an open-air natural environment for 4 months; the piled ore raw material was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 300mT to adsorb and remove impurities; the ore powder was washed twice with 0.02mmol / L hydrochloric acid solution, drained and washed with deionized water to pH 5.6; 20mL of deionized water was used to prepare a suspension, and centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 20mL of a mixture of concentrated sulfuric acid and permanganate (5g:0.2g) to form an ore base material 2 and dried for standby use;

[0050] 80g of the above-mentioned ore base material 1 is added to 5g of the connecting material and dispersed evenly, 2g of tortoise shell glue, 0.01g of linden honey, 2g of 80-mesh titanium dioxide powder, and 0.2g of Simao rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 1 year, and the deteriorated area is manually removed to obtain;

[0051] The preparation method of the connecting material in the formula is as follows:

[0052] 0.1 mol of dimethylbiphenyl diisocyanate and 0.08 mol of polybutylene adipate (diol) were fully dissolved in 15 mL of dioxane, and then the temperature was raised to 60°C, 0.1 mmol of 1,4-butanediol, 0.01 mg of dibutyltin dilaurate and 3 g of ore base material 2 were added, and the mixture was kept warm for 2 hours; the system temperature was adjusted to 41°C, 0.07 mol of oxalyl chloride and 0.2 mg of 4-pyrrolidinopyridine were added, and the mixture was kept warm for 8 hours; the system temperature was adjusted to 5°C, 0.04 mol of 4-methylphenylethylamine was added, and the mixture was kept warm for 5 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore-based grafted polyurethane, i.e., connecting material.

[0053] Example 3

[0054] A preparation method of an antique pigment and its formula composition are as follows:

[0055] 10.0g of lapis lazuli ore raw material was crushed after primary screening, 2.3g of sodium thiosulfate was added, stirred evenly and piled in an open-air natural environment for 50 months; the piled ore raw material was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 760mT to adsorb and remove impurities; the ore powder was washed 9 times with 0.5mmol / L hydrochloric acid solution, drained and washed with deionized water to pH 7.1; 200mL of deionized water was used to prepare a suspension, and centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 100mL of a mixture of concentrated sulfuric acid and permanganate (5g:0.2g) to form an ore base material 2, which was dried and used for standby;

[0056] 80g of the above-mentioned ore base material 1 is added to 18g of the connecting material and dispersed evenly, 10g of tortoise shell glue, 0.50g of linden honey, 10g of 2000 mesh titanium dioxide powder, and 0.9g of Simao rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 5 years, and the deteriorated area is manually removed to obtain;

[0057] The preparation method of the connecting material in the formula is as follows:

[0058] 0.1 mol of dimethylbiphenyl diisocyanate and 0.25 mol of polybutylene adipate (diol) were fully dissolved in 500 mL of dioxane, and then the temperature was raised to 210°C, 12.8 mmol of 1,4-butanediol, 0.93 mg of dibutyltin dilaurate and 15 g of ore base material 2 were added, and the mixture was kept warm for 17 hours; the system temperature was adjusted to 115°C, 0.14 mol of oxalyl chloride and 15 mg of 4-pyrrolidinopyridine were added, and the mixture was kept warm for 16 hours; the system temperature was adjusted to 36°C, 0.50 mol of 4-methylphenylethylamine was added, and the mixture was kept warm for 45 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore-based grafted polyurethane, i.e., connecting material.

[0059] Example 4

[0060] A preparation method of an antique pigment and its formula composition are as follows:

[0061] 10.0g of Kongqing ore raw material was crushed after primary screening, 0.6g of sodium carbonate was added, stirred evenly and piled in an open-air natural environment for 5 months; the piled ore raw material was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 310mT to adsorb and remove impurities; the ore powder was washed 3 times with 0.03mmol / L nitric acid solution, drained and washed with deionized water to pH 5.7; 21mL of deionized water was then used to prepare a suspension, and the suspension was centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 25mL of a mixture of concentrated nitric acid and perchloric acid (5g:15.5g) to form an ore base material 2 and dried for standby use;

[0062] 80g of the above-mentioned ore base material 1 is added to 6g of the connecting material and dispersed evenly, 3g of egg white, 0.02g of rape honey, 3g of 100-mesh calcium bicarbonate powder, and 0.3g of horsetail rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 2 years, and the deteriorated area is manually removed to obtain;

[0063] The preparation method of the connecting material in the formula is as follows:

[0064] 0.1 mol of diphenylmethane-4,4'-diisocyanate and 0.09 mol of polybutadiene diol were fully dissolved in 16 mL of ethyl acetate, and then the temperature was raised to 62°C, and 0.2 mmol of ethylene glycol, 0.02 mg of phenylmercuric acetate and 4 g of ore base material 2 were added and kept warm for 3 hours; the system temperature was adjusted to 42°C, 0.08 mol of thionyl chloride and 0.3 mg of 4-dimethylaminopyridine were added, and the temperature was kept warm for 10 hours; the system temperature was adjusted to 6°C, 0.05 mol of ethylenediamine was added, and the temperature was kept warm for 6 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore-based grafted polyurethane, i.e., connecting material.

[0065] Example 5

[0066] A preparation method of an antique pigment and its formula composition are as follows:

[0067] 10.0g of dianqingshi ore raw material was crushed after primary screening, 0.8g of potassium sulfite was added, stirred evenly and piled in an open-air natural environment for 6 months; the ore raw material after piling was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 320mT to adsorb and remove impurities; the ore powder was washed 4 times with 0.04mmol / L sulfuric acid solution, drained and washed with deionized water to pH 5.8; 40mL of deionized water was then used to prepare a suspension, and centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 41mL of a mixture of perchloric acid and metaphosphoric acid (1g:15g) to form an ore base material 2 and dried for standby use;

[0068] 80g of the above-mentioned ore base material 1 is added to 7g of the connecting material and dispersed evenly, 4g of fish maw boiled extract, 0.05g of vitex honey, 5g of 120 mesh white carbon black powder, and 0.5g of wetland rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 4 years, and the deteriorated area is manually removed to obtain;

[0069] The preparation method of the connecting material in the formula is as follows:

[0070] 0.1 mol of p-phenylene diisocyanate and 0.10 mol of polycaprolactone (diol) were fully dissolved in 22 mL of benzene, and then the temperature was raised to 74°C, and 0.9 mmol of diethylene glycol, 0.08 mg of phenylmercuric propionate and 5 g of ore base material 2 were added and kept warm for 4 hours; the system temperature was adjusted to 46°C, 0.09 mol of phosphorus trichloride and 1.5 mg of N-hydroxysuccinimide were added, and the temperature was kept warm for 11 hours; the system temperature was adjusted to 13°C, 0.06 mol of 1,3-propylenediamine was added, and the temperature was kept warm for 7 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore-based grafted polyurethane, i.e., connecting material.

[0071] Example 6

[0072] A preparation method of an antique pigment and its formula composition are as follows:

[0073] 10.0g of Yunnan bluestone ore raw material was crushed after primary screening, 0.9g of sodium bicarbonate was added, stirred evenly and piled in an open-air natural environment for 7 months; the ore raw material after piling was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 380mT to adsorb and remove impurities; the ore powder was washed with 0.14mmol / L hydrochloric acid solution for 6 times, drained and washed with deionized water to pH 6.0; 80mL of deionized water was used to prepare a suspension, and centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 25mL of a mixture of concentrated sulfuric acid and fluoroboric acid (5g:2g) to form an ore base material 2 and dried for standby use;

[0074] 80g of the above-mentioned ore base material 1 is added to 7g of the connecting material and dispersed evenly, 5g of animal leather boiled extract, 0.02g of loquat honey, 5g of 120-mesh alumina powder, and 0.5g of long-leaf rosin are added and dispersed evenly again, placed in a cool and dry environment for aging for 4 years, and the deteriorated area is manually removed to obtain;

[0075] The preparation method of the connecting material in the formula is as follows:

[0076] 0.1 mol of hexamethylene diisocyanate and 0.11 mol of polytetramethylene glycol were fully dissolved in 310 mL of toluene, and then the temperature was raised to 65°C, 2.5 mmol of neopentyl glycol, 0.64 mg of stannous octoate and 7 g of ore base material 2 were added, and the mixture was kept warm for 5 hours; the system temperature was adjusted to 47°C, 0.10 mol of phosphorus oxychloride and 0.9 mg of 1-hydroxybenzotriazole were added, and the mixture was kept warm for 10 hours; the system temperature was adjusted to 15°C, 0.50 mol of n-butylamine was added, and the mixture was kept warm for 28 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore base material grafted polyurethane, i.e., connecting material.

[0077] Example 7

[0078] A preparation method of an antique pigment and its formula composition are as follows:

[0079] 10.0 g of malachite ore raw material was crushed after primary screening, 1.0 g of potassium sulfate was added, stirred evenly and piled in an open-air natural environment for 10 months; the piled ore raw material was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 395 mT to adsorb and remove impurities; the ore powder was washed with 0.4 mmol / L hydrochloric acid solution for 6 times, drained and washed with deionized water to pH 6.2; 180 mL of deionized water was then used to prepare a suspension, and centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 74 mL of a mixture of concentrated nitric acid and 2,4,6-trinitrophenol (3 g:0.8 g) to form an ore base material 2, which was dried and used for standby;

[0080] 80g of the above-mentioned ore base material 1 is added to 12g of the connecting material and dispersed evenly, 5g of beeswax, 0.09g of acacia honey, 9g of 500-mesh alumina powder, and 0.8g of Cuban rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 4 years, and the deteriorated area is manually removed to obtain;

[0081] The preparation method of the connecting material in the formula is as follows:

[0082] 0.1 mol 1,5-naphthalene diisocyanate and 0.20 mol polytetramethylene glycol were fully dissolved in 330 mL xylene, and then the temperature was raised to 204°C, 9.8 mmol 3,5-dimethylthiotoluenediamine, 0.43 mg stannous octoate and 7 g ore base material 2 were added, and the mixture was kept warm for 10 hours; the system temperature was adjusted to 64°C, 0.11 mol diketone and 7 mg 1-hydroxybenzotriazole were added, and the mixture was kept warm for 12 hours; the system temperature was adjusted to 6°C, 0.40 mol 1-phenylpropane-1-amine was added, and the mixture was kept warm for 20 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore-based grafted polyurethane, i.e., connecting material.

[0083] Example 8

[0084] A preparation method of an antique pigment and its formula composition are as follows:

[0085] 10.0g of cinnabar ore raw material was crushed after primary screening, 1.1g of sodium hypochlorite was added, stirred evenly and piled in an open-air natural environment for 14 months; the piled ore raw material was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 405mT to adsorb and remove impurities; the ore powder was washed with 0.4mmol / L sulfuric acid solution for 7 times, drained and washed with deionized water to pH 7.0; 104mL of deionized water was then used to prepare a suspension, and the suspension was centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 22mL of perchloric acid and concentrated hydrochloric acid (3g:8g) to form an ore base material 2, which was dried and used for standby;

[0086] 80g of the above-mentioned ore base material 1 is added to 12g of the connecting material and dispersed evenly, 9g of agar, 0.33g of Sophora japonica honey, 8g of 200-mesh montmorillonite powder, and 0.8g of torch rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 4 years, and the deteriorated area is manually removed to obtain;

[0087] The preparation method of the connecting material in the formula is as follows:

[0088] 0.1 mol of 4,4-diisocyanate dicyclohexylmethane and 0.21 mol of polypropylene glycol were fully dissolved in 250 mL of dimethylformamide, and then the temperature was raised to 200° C. 8.7 mmol of 3,5-diethyltoluenediamine, 0.82 mg of tetramethylpropylenediamine and 5 g of ore base material 2 were added and kept warm for 7 hours; the system temperature was adjusted to 52° C., 0.13 mol of phthalic anhydride and 3 mg of 1-hydroxy-7-azabenzotriazole were added and kept warm for 13 hours; the system temperature was adjusted to 22° C., 0.43 mol of 3-aminoethylbenzene was added and kept warm for 18 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore-based grafted polyurethane, i.e., connecting material.

[0089] Example 9

[0090] A preparation method of an antique pigment and its formula composition are as follows:

[0091] 10.0g of Zhuliao ore raw material was crushed after primary screening, 1.2g of trisodium phosphate was added, stirred evenly and piled in an open-air natural environment for 20 months; the piled ore raw material was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 550mT to adsorb and remove impurities; the ore powder was washed 8 times with 0.5mmol / L sulfuric acid solution, drained and washed with deionized water to pH 6.5; 140mL of deionized water was then used to prepare a suspension, and centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 88mL of a mixture of metaphosphoric acid and permanganate (7g:0.2g) to form an ore base material 2 and dried for standby use;

[0092] 80g of the above-mentioned ore base material 1 is added to 14g of the connecting material and dispersed evenly, 2g of peach gum, 0.50g of rape honey, 6g of 80-mesh pearl powder, and 0.8g of torch rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 2 years, and the deteriorated area is manually removed to obtain;

[0093] The preparation method of the connecting material in the formula is as follows:

[0094] 0.1 mol toluene-2,6-diisocyanate and 0.21 mol polytetrahydrofuran were fully dissolved in 420 mL dimethylformamide, and then the temperature was raised to 65°C, and 10.8 mmol triethanolamine, 0.008 mg N-methylimidazole and 14 g ore base material 2 were added and kept warm for 10 hours; the system temperature was adjusted to 72°C, 0.14 mol N,N-diisopropylcarbodiimide and 13 mg 1-hydroxy-7-azabenzotriazole were added, and the temperature was kept warm for 15 hours; the system temperature was adjusted to 22°C, 0.50 mol 3-methyl-1-phenylethylbutylamine was added, and the temperature was kept warm for 12 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore-based grafted polyurethane, i.e., connecting material.

[0095] Example 10

[0096] A preparation method of an antique pigment and its formula composition are as follows:

[0097] 10.0g of pyroxene ore raw material was crushed after primary screening, 1.3g of sodium carbonate was added, stirred evenly and piled in an open-air natural environment for 34 months; the ore raw material after piling was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 640mT to adsorb and remove impurities; the ore powder was washed 8 times with 0.3mmol / L nitric acid solution, drained and washed with deionized water to pH 6.9; 180mL of deionized water was then used to prepare a suspension, and the suspension was centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 90mL of a mixture of perbromic acid and thiocyanate (5g:7g) to form an ore base material 2 and dried for standby use;

[0098] 80g of the above-mentioned ore base material 1 is added to 14g of the connecting material and dispersed evenly, 6g of guar gum, 0.07g of loquat honey, 8g of 1000 mesh shell powder, and 0.5g of wetland rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 2 years, and the deteriorated area is manually removed to obtain;

[0099] The preparation method of the connecting material in the formula is as follows:

[0100] 0.1 mol toluene-2,6-diisocyanate and 0.21 mol polytetramethylene ether glycol were fully dissolved in 450 mL ethyl acetate, and then the temperature was raised to 152°C, and 10.7 mmol ethylene glycol, 0.82 mg N-methylmorpholine and 10 g ore base material 2 were added and kept warm for 13 hours; the system temperature was adjusted to 88°C, 0.11 mol methacrylic acid and 12.2 mg 1-hydroxy-7-azabenzotriazole were added, and the temperature was kept warm for 14 hours; the system temperature was adjusted to 13°C, 0.50 mol 4-methylphenylethylamine was added, and the temperature was kept warm for 7 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore-based grafted polyurethane, i.e., connecting material.

[0101] Embodiment 11

[0102] A preparation method of an antique pigment and its formula composition are as follows:

[0103] 10.0g of black ash ore raw material was crushed after primary screening, 1.4g of potassium sulfite was added, stirred evenly and piled in an open-air natural environment for 16 months; the piled ore raw material was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 450mT to adsorb and remove impurities; the ore powder was washed 8 times with 0.28mmol / L sulfuric acid solution, drained and washed with deionized water to pH 7.0; 150mL of deionized water was then used to prepare a suspension, and centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 48mL of a mixture of concentrated sulfuric acid, concentrated nitric acid and osmic acid (6g:5g:0.2g) to form an ore base material 2 and dried for standby use;

[0104] 80g of the above-mentioned ore base material 1 is added to 8g of the connecting material and dispersed evenly, 3g of sesame gum, 0.42g of rape honey, 7g of 1500 mesh shell powder, and 0.9g of long-leaf rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 2 years, and the deteriorated area is manually removed to obtain;

[0105] The preparation method of the connecting material in the formula is as follows:

[0106] 0.1 mol of p-phenylene diisocyanate and 0.18 mol of polypropylene glycol were fully dissolved in 470 mL of dimethylformamide, and then the temperature was raised to 83°C, 10.8 mmol of 2,4-diamino-3,5-dimethylthiochlorobenzene, 0.33 mg of N-methylmorpholine and 3 g of ore base material 2 were added, and the temperature was kept for 16 hours; after adjusting the system temperature to 90°C, 0.09 mol of 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate and 13 mg of 1-hydroxy-7-azabenzotriazole were added, and the temperature was kept for 15 hours; the system temperature was adjusted to 30°C, 0.50 mol of m-methylphenylethylamine was added, and the temperature was kept for 40 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore-based grafted polyurethane, i.e., connecting material.

[0107] Example 12

[0108] A preparation method of an antique pigment and its formula composition are as follows:

[0109] 10.0 g of chalk ore raw material was crushed after primary screening, 1.5 g of sodium bicarbonate was added, stirred evenly and piled in an open-air natural environment for 28 months; the piled ore raw material was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 700 mT to adsorb and remove impurities; the ore powder was washed with 0.5 mmol / L sulfuric acid solution for 6 times, drained and washed with deionized water to pH 6.6; 172 mL of deionized water was used to prepare a suspension, and centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 87 mL of a mixture of chlorolead acid, metaphosphoric acid and 2,4,6-trinitrobenzoic acid (4 g: 0.3 g: 11.5 g) to form an ore base material 2 and dried for standby use;

[0110] 80g of the above-mentioned ore base material 1 is added to 17g of the connecting material and dispersed evenly, 4g of fennel gum, 0.38g of acacia honey, 8g of 80-mesh calcium bicarbonate powder, and 0.8g of Cuban rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 4 years, and the deteriorated area is manually removed to obtain the product;

[0111] The preparation method of the connecting material in the formula is as follows:

[0112] 0.1 mol of 4,4-diisocyanate dicyclohexylmethane and 0.22 mol of polyoxypropylene glycol were fully dissolved in 400 mL of ethyl acetate, and then the temperature was raised to 67°C, and 10.3 mmol of neopentyl glycol, 0.53 mg of 1,4-dimethylpiperazine and 12 g of ore base material 2 were added and kept warm for 11 hours; the system temperature was adjusted to 92°C, and 0.09 mol of O-benzotriazole-tetramethyluronium hexafluorophosphate and 3 mg of 1-hydroxy-7-azabenzotriazole were added and kept warm for 9 hours; the system temperature was adjusted to 33°C, and 0.11 mol of m-methylphenylethylamine was added and kept warm for 40 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore-based grafted polyurethane, i.e., connecting material.

[0113] Embodiment 13

[0114] A preparation method of an antique pigment and its formula composition are as follows:

[0115] 10.0g of the raw material of the quartzite ore was crushed after primary screening, 1.6g of sodium hypochlorite was added, stirred evenly and piled in an open-air natural environment for 28 months; the raw material of the ore after piling was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 455mT to adsorb and remove impurities; the ore powder was washed 8 times with a 0.45mmol / L nitric acid solution, drained and washed with deionized water to pH 6.3; 154mL of deionized water was then used to prepare a suspension, and the suspension was centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 81mL of a mixture of perchloric acid, hydrobromic acid and KMD acid (6g:0.2g:13g) to form an ore base material 2 and dried for standby use;

[0116] 80g of the above-mentioned ore base material 1 is added to 6g of the connecting material and dispersed evenly, 10g of eucommia gum, 0.33g of linden honey, 7g of 2000 mesh calcium bicarbonate powder, and 0.7g of torch rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 2 years, and the deteriorated area is manually removed to obtain;

[0117] The preparation method of the connecting material in the formula is as follows:

[0118] 0.1 mol toluene-2,6-diisocyanate and 0.22 mol polytetramethylene ether glycol were fully dissolved in 187 mL benzene, and then the temperature was raised to 162° C., 10.4 mmol trimethylolpropane, 0.89 mg di(dodecylsulfide) dibutyltin and 10 g ore base material 2 were added, and the temperature was kept for 4 hours; after adjusting the system temperature to 102° C., 0.14 mol O-benzotriazole-N,N,N',N'-tetramethyluronium tetrafluoroboric acid and 7 mg 1-hydroxy-7-azabenzotriazole were added, and the temperature was kept for 10 hours; the system temperature was adjusted to 12° C., 0.05 mol m-methylphenylethylamine was added, and the temperature was kept for 41 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore-based grafted polyurethane, i.e., connecting material.

[0119] Embodiment 14

[0120] A preparation method of an antique pigment and its formula composition are as follows:

[0121] 10.0g of Biqing ore raw material was crushed after primary screening, 1.7g of trisodium phosphate was added, stirred evenly and piled in an open-air natural environment for 40 months; the piled ore raw material was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 740mT to adsorb and remove impurities; the ore powder was washed 8 times with 0.49mmol / L nitric acid solution, drained and washed with deionized water to pH 6.1; 130mL of deionized water was used to prepare a suspension, and centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 80mL of a mixture of trifluoroacetic acid, trichloroacetic acid and perfluorosulfonic acid resin (2g:3g:17g) to form an ore base material 2 and dried for standby use;

[0122] 80g of the above-mentioned ore base material 1 is added to 6g of the connecting material and dispersed evenly, 10g of glutinous rice soup, 0.24g of Sophora japonica honey, 7g of 1800 mesh alumina powder, and 0.9g of Simao rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 4 years, and the deteriorated area is manually removed to obtain;

[0123] The preparation method of the connecting material in the formula is as follows:

[0124] 0.1 mol of o-phenylenediisocyanate and 0.19 mol of polyoxypropylene glycol were fully dissolved in 330 mL of ethyl acetate, and then the temperature was raised to 154° C., 6.7 mmol of neopentyl glycol, 0.28 mg of potassium acetate and 4 g of ore base material 2 were added, and the mixture was kept warm for 13 hours; the system temperature was adjusted to 88° C., 0.08 mol of methacrylic anhydride and 7 mg of 4-dimethylaminopyridine were added, and the mixture was kept warm for 10 hours; the system temperature was adjusted to 29° C., 0.06 mol of m-methylphenylethylamine was added, and the mixture was kept warm for 23 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore base material grafted polyurethane, i.e., connecting material.

[0125] Embodiment 15

[0126] A preparation method of an antique pigment and its formula composition are as follows:

[0127] 10.0g of the raw material of the blue ore was crushed after primary screening, 1.8g of sodium hypochlorite was added, stirred evenly and piled in an open-air natural environment for 14 months; the raw material of the piled ore was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 610mT to adsorb and remove impurities; the ore powder was washed 8 times with a 0.11mmol / L sulfuric acid solution, drained and washed with deionized water to pH 7.0; 154mL of deionized water was then used to prepare a suspension, and the suspension was centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 33mL of a mixture of fluorosilicic acid, oxalic acid and Tribble volatile acid (5g:1g:17g) to form an ore base material 2 and dried for standby use;

[0128] 80g of the above-mentioned ore base material 1 is added to 8g of the connecting material and dispersed evenly, 6g of sesame glue, 0.38g of acacia honey, 8g of 80-mesh montmorillonite powder, and 0.9g of horsetail rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 3 years, and the deteriorated area is manually removed to obtain;

[0129] The preparation method of the connecting material in the formula is as follows:

[0130] 0.1 mol of dimethylbiphenyl diisocyanate and 0.25 mol of polyethylene adipate (propylene glycol) ester (diol) were fully dissolved in 100 mL of dimethylformamide, and then the temperature was raised to 202°C, 4.5 mmol of 3,5-diethyltoluenediamine, 0.91 mg of tetramethylethylenediamine and 6 g of ore base material 2 were added, and the mixture was kept warm for 5 hours; after adjusting the system temperature to 111°C, 0.14 mol of methacryloyl chloride and 7 mg of 1-hydroxybenzotriazole were added, and the mixture was kept warm for 13 hours; after adjusting the system temperature to 10°C, 0.30 mol of 3-methyl-1-phenylethylbutylamine was added, and the mixture was kept warm for 21 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore-based grafted polyurethane, i.e., a connecting material.

[0131] Example 16

[0132] A preparation method of an antique pigment and its formula composition are as follows:

[0133] 10.0g of blue ore raw material was crushed after primary screening, 1.9g of sodium carbonate was added, stirred evenly and piled in an open-air natural environment for 41 months; the piled ore raw material was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 702mT to adsorb and remove impurities; the ore powder was washed 7 times with 0.29mmol / L hydrochloric acid solution, drained and washed with deionized water to pH 6.2; 100mL of deionized water was used to prepare a suspension, and centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 50mL of a mixture of fluorosilicic acid, chlorolead acid, metaphosphoric acid and benzenesulfonic acid (5g:1g:8g:1.2g) to form an ore base material 2 and dried for standby use;

[0134] 80g of the above-mentioned ore base material 1 is added to 7g of the connecting material and dispersed evenly, 3g of peach gum, 0.24g of rapeseed honey, 7g of 1000 mesh pearl powder, and 0.6g of long-leaf rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 4 years, and the deteriorated area is manually removed to obtain;

[0135] The preparation method of the connecting material in the formula is as follows:

[0136] 0.1 mol toluene-2,6-diisocyanate and 0.22 mol polypropylene glycol were fully dissolved in 160 mL xylene, and then the temperature was raised to 144° C., 0.2 mmol N,N-bis(2-hydroxypropyl)aniline, 0.83 mg tetramethylethylenediamine and 11 g ore base material 2 were added, and the temperature was kept for 13 hours; after adjusting the system temperature to 52° C., 0.14 mol O-benzotriazole-tetramethyluronium hexafluorophosphate and 13 mg 1-hydroxybenzotriazole were added, and the temperature was kept for 9 hours; after adjusting the system temperature to 25° C., 0.04 mol 3-methyl-1-phenylethylbutylamine was added, and the temperature was kept for 41 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore-based grafted polyurethane, i.e., connecting material.

[0137] Embodiment 17

[0138] A preparation method of an antique pigment and its formula composition are as follows:

[0139] 10.0g of male concentrate ore raw material was crushed after primary screening, 2.0g of potassium sulfite was added, stirred evenly and piled in an open-air natural environment for 17 months; the ore raw material after stacking was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 751mT to adsorb and remove impurities; the ore powder was washed 4 times with 0.5mmol / L sulfuric acid solution, drained and washed with deionized water to pH 6.9; 30mL of deionized water was then used to prepare a suspension, and centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 24mL of a mixture of perbromic acid, fluorosilicic acid, benzenesulfonic acid and fluoroantimonysulfonic acid (8g:0.2g:22g:19g) to form an ore base material 2 and dried for standby use;

[0140] 80g of the above-mentioned ore base material 1 is added to 15g of the connecting material and dispersed evenly, 3g of sesbania gum, 0.09g of loquat honey, 6g of 2000 mesh calcium bicarbonate powder, and 0.3g of torch rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 4 years, and the deteriorated area is manually removed to obtain;

[0141] The preparation method of the connecting material in the formula is as follows:

[0142] 0.1 mol of o-phenylenediisocyanate and 0.19 mol of polyoxytetramethylene glycol were fully dissolved in 430 mL of dimethylformamide, and then the temperature was raised to 166° C. 8.3 mmol of isophorone diamine, 0.69 mg of dibutyltin dilaurate and 9 g of ore base material 2 were added and kept warm for 8 hours; the system temperature was adjusted to 82° C., 0.11 mol of methacryloyl chloride and 9.2 mg of 1-hydroxy-7-azabenzotriazole were added and kept warm for 10 hours; the system temperature was adjusted to 11° C., 0.04 mol of ethylenediamine was added and kept warm for 42 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore-based grafted polyurethane, i.e., connecting material.

[0143] Embodiment 18

[0144] A preparation method of an antique pigment and its formula composition are as follows:

[0145] 10.0 g of bean green ore raw material was crushed after primary screening, 2.1 g of sodium hypochlorite was added, stirred evenly and piled in an open-air natural environment for 31 months; the piled ore raw material was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 580 mT to adsorb and remove impurities; the ore powder was washed 7 times with 0.33 mmol / L nitric acid solution, drained and washed with deionized water to pH 6.0; 188 mL of deionized water was then used to prepare a suspension, and the suspension was centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 23 mL of a mixture of 2,4,6-trinitrophenol, 2,4,6-trinitrobenzoic acid, trifluoroacetic acid, trichloroacetic acid and Tribull volatile acid (5 g: 0.2 g: 11 g: 12 g: 8.6 g) to form an ore base material 2 and dried for standby use;

[0146] 80g of the above-mentioned ore base material 1 is added to 16g of the connecting material and dispersed evenly, 9g of animal leather boiled extract, 0.31g of rape honey, 7g of 1000 mesh pearl powder, and 0.5g of long-leaf rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 2 years, and the deteriorated area is manually removed to obtain;

[0147] The preparation method of the connecting material in the formula is as follows:

[0148] 0.1 mol of isophorone diisocyanate and 0.19 mol of polyethylene adipate (propylene glycol) ester (diol) were fully dissolved in 84 mL of toluene, and then the temperature was raised to 63°C, 7.3 mmol of 3,5-dimethylthiotoluenediamine, 0.44 mg of tetramethylethylenediamine and 10 g of ore base material 2 were added, and the mixture was kept warm for 6 hours; after adjusting the system temperature to 44°C, 0.14 mol of O-benzotriazole-tetramethyluronium hexafluorophosphate and 4.7 mg of 1-hydroxy-7-azabenzotriazole were added, and the mixture was kept warm for 13 hours; after adjusting the system temperature to 12°C, 0.50 mol of 3-methyl-1-phenylethylbutylamine was added, and the mixture was kept warm for 12 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore-based grafted polyurethane, i.e., connecting material.

[0149] Embodiment 19

[0150] A preparation method of an antique pigment and its formula composition are as follows:

[0151] 10.0g of yellow ore raw material was crushed after primary screening, 2.2g of trisodium phosphate was added, stirred evenly and piled in an open-air natural environment for 8 months; the piled ore raw material was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 556mT to adsorb and remove impurities; the ore powder was washed 8 times with 0.17mmol / L sulfuric acid solution, drained and washed with deionized water to pH 6.8; 188mL of deionized water was then used to prepare a suspension, and centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 60mL of a mixture of concentrated nitric acid, concentrated hydrochloric acid, hydrobromic acid, thiocyanic acid and 2,4,6-trinitrophenol (1g:0.5g:16g:7g:10g) to form an ore base material 2 and dried for standby use;

[0152] 80g of the above-mentioned ore base material 1 is added to 10g of the connecting material and dispersed evenly, 3g of fish maw boiled extract, 0.50g of Sophora japonica honey, 7g of 80-mesh alumina powder, and 0.9g of torch rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 2 years, and the deteriorated area is manually removed to obtain the product;

[0153] The preparation method of the connecting material in the formula is as follows:

[0154] 0.1 mol of diphenylmethane-4,4'-diisocyanate and 0.11 mol of polytetramethylene glycol were fully dissolved in 130 mL of dimethylformamide, and then the temperature was raised to 192°C, 12.8 mmol of 3,5-dimethylthiotoluenediamine, 0.72 mg of potassium acetate and 6 g of ore base material 2 were added, and the mixture was kept warm for 8 hours; after adjusting the system temperature to 52°C, 0.14 mol of methacrylic anhydride and 6.4 mg of 1-hydroxy-7-azabenzotriazole were added, and the mixture was kept warm for 9 hours; after adjusting the system temperature to 27°C, 0.04 mol of 1-naphthylmethylamine was added, and the mixture was kept warm for 18 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore base material grafted polyurethane, i.e., connecting material.

[0155] Embodiment 20

[0156] A preparation method of an antique pigment and its formula composition are as follows:

[0157] 10.0g of orpiment ore raw material was crushed after primary screening, 2.3g of sodium thiosulfate was added, stirred evenly and piled in an open-air natural environment for 21 months; the ore raw material after piling was crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 604mT to adsorb and remove impurities; the ore powder was washed 8 times with 0.21mmol / L hydrochloric acid solution, drained and washed with deionized water to pH 5.9; 101mL of deionized water was then used to prepare a suspension, and centrifuged to separate the solid and liquid; the supernatant was dried to form an ore base material 1, and the solid sediment was dried and oxidized with 58mL of hydroiodic acid, chlorolead acid, metaphosphoric acid, fluoroboric acid, trifluoroacetic acid, methanesulfonic acid, KMD acid, perfluorosulfonic acid resin and Tribble volatile acid mixture (5g:1g:7g:17g:6g:0.5g:150mg:10mg:10g) to form an ore base material 2 and dried for standby use;

[0158] 80g of the above-mentioned ore base material 1 is added to 17g of the connecting material and dispersed evenly, 6g of beeswax, 0.49g of loquat honey, 3g of 1800 mesh white carbon black powder, and 0.8g of long-leaf rosin are added and dispersed evenly again, and placed in a cool and dry environment for aging for 2 years, and the deteriorated area is manually removed to obtain;

[0159] The preparation method of the connecting material in the formula is as follows:

[0160] 0.1 mol of 4,4-diisocyanate dicyclohexylmethane and 0.05 mol of polyethylene glycol (adipate) propylene glycol (adipate) ester (diol) were fully dissolved in 170 mL of toluene, and then the temperature was raised to 149° C., 0.1 mmol of diethylene glycol, 0.85 mg of potassium acetate and 5 g of ore base material 2 were added, and the mixture was kept warm for 13 hours; after adjusting the system temperature to 62° C., 0.11 mol of methacrylic acid and 15 mg of 1-hydroxy-7-azabenzotriazole were added, and the mixture was kept warm for 10 hours; after adjusting the system temperature to 12° C., 0.04 mol of 1-aminopentane was added, and the mixture was kept warm for 32 minutes; the system temperature was adjusted to room temperature and most of the solvent was removed to obtain ore base material grafted polyurethane, i.e., connecting material.

[0161] Experimental results and analysis

[0162] (1) About 0.2 g of the pigment sample was weighed and dispersed evenly with 50 mL of castor oil. The internal microstructure of the dispersion was characterized by transmission electron microscopy. Figure 2 As shown, (a) represents Example 1, and (b) represents Example 20. It can be seen that both dispersions contain obvious opaque spherical particles with uniform particle size and an average particle size of less than 0.1 μm, indicating that the pigment particles prepared by the technical solution of the present invention are fine and uniform, and can support the processing and expression of modeling details during painting. This is mainly due to the fact that the ultrafine particles obtained from the ore raw materials have a small particle size and can be directly used as one of the components of antique pigments. At the same time, the medium-fine particles obtained from the ore raw materials have a reduced particle size after activation, and a hydroxyl structure is formed on the surface, which can participate in the polyurethane copolymerization reaction and obtain an organic / inorganic hybrid material. In the polyurethane chain growth stage, affected by the steric hindrance effect, the length of the organic chain segment tends to be equal, so the particle size of the ore-based grafted polyurethane obtained is relatively uniform. In addition, other components such as colloid, honey, filler, rosin, etc. in the antique pigment are not in a granular state or contain particles with a small particle size. Therefore, when characterizing the internal microstructure of the antique pigment sample as a whole, it can be observed that the particle size is small and the particle size is relatively uniform;

[0163] (2) Antique pigments were applied to canvas by traditional brush painting and spraying, and the microstructure of the pigment surface was characterized, such as Figure 3 As shown, (A) and (B) are traditional pen painting, and (C) and (D) are spraying. It can be seen that the particles are regularly and closely arranged in the traditional pen painting, which is mainly due to the relatively uniform particles of the antique pigment itself, which is the basis for the close arrangement of the particles. At the same time, the binder contained is an organic / inorganic hybrid structure, which can be very compatible with other components. The polyurethane chain segments of the antique pigment are stretched and arranged in a certain direction as the brush strokes move; the pigment surface obtained by spraying is relatively loose and has obvious granular structures stacked on each other, but it can still achieve relatively close bonding, which is mainly due to the good encapsulation performance of the colloid and polyurethane chain segments in the antique pigment for other components;

[0164] (3) The surface of the antique pigment and the surface of the reference pigment were tested respectively before and after ultraviolet irradiation. They were uniformly coated on the surface of white cardboard with a size of 10 cm*10 cm, with a coating thickness of about 0.5 mm, and placed under vertical ultraviolet light for 24 hours. The color difference data of the coating before and after ultraviolet irradiation were detected and recorded, as shown in Table 1. It can be seen that the lightness change, red-green color cast, and yellow-blue color cast of the reference were large, and the overall color difference value reached 11.02. The lightness change, red-green color cast, and yellow-blue color cast of the antique pigments of Examples 1, 5, and 10 were small, and the overall color difference value was generally ≤0.9. This is mainly due to the fact that the main color-developing substance used in the present invention is derived from natural conditions and has good ultraviolet light tolerance. At the same time, other components such as colloid, honey, filler, and rosin have almost no color or good ultraviolet light tolerance. Therefore, the antique pigment finally prepared exhibits excellent anti-ultraviolet light discoloration performance;

[0165] Table 1. Color difference data change value after the pigment surface is irradiated by ultraviolet light

[0166]

[0167] (4) Using an ink friction tester (2000 model, Sutherland, USA) at 4 pounds of pressure and 85 revolutions per minute, the color fading condition of the pigment layer of the sample obtained in (3) after a 1-minute friction test was tested. Figure 4 As shown. It can be seen that the reference pigment has obvious discoloration marks after friction, while the antique pigment of Example 1 of the present invention does not discolor obviously or the discoloration marks are negligible after friction. This is mainly due to the fact that the ore base material 1 separated from the ore raw material has a small particle size and can be well wrapped by colloid and honey, and the ore base material 2 separated is modified by polyurethane to form a long molecular chain coating on the particle surface. At the same time, the rosin in the component has a good lubricating effect on the coating. Therefore, the antique pigment finally obtained does not discolor obviously or the discoloration marks are negligible during the friction test;

[0168] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing an antique pigment, characterized in that: The steps include: (1) The ore raw material is crushed after primary screening, and a soluble alkaline salt is added to stir evenly and piled in an open-air natural environment for 4 to 50 months; the piled ore raw material is crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 300 to 760 mT to adsorb and remove impurities; the ore powder is washed with a dilute acid solution for 2 to 9 times, drained and washed with water to a pH of 5.6 to 7.1, and then prepared with water to form a suspension, and centrifuged to separate the solid and liquid; the supernatant is dried to form an ore base material 1, and the solid sediment is dried and oxidized with a mixed acid to form an ore base material 2 and dried; (2) adding the ore base material 1 to the connecting material and dispersing it uniformly, adding colloid, honey, filler and rosin and dispersing it uniformly again, placing it in a cool and dry environment for aging for 1 to 5 years, and removing the deteriorated area to obtain; The preparation method of the connecting material is as follows: fully dissolve the polyisocyanate and polyol with a solvent, add the solvent, heat it to 60-210°C, add a chain extender, a catalyst 1 and an ore base material 2, keep it warm for 2-17 hours, adjust the system temperature to 41-115°C, add an activator and a catalyst 2, keep it warm for 8-16 hours, adjust the system temperature to 5-36°C, add a passivator and keep it warm for 5-45 minutes, adjust the system temperature to room temperature and remove most of the solvent to obtain an ore base material grafted polyurethane, i.e., a connecting material; the polyisocyanate is dimethyl diphenyl diisocyanate, diphenylmethane-4,4'-diisocyanate, p-phenylene diisocyanate, hexamethylene diisocyanate, 1,5-naphthalene diisocyanate, isophorone diisocyanate Acid ester, 4,4-diisocyanate dicyclohexylmethane, o-phenylenediisocyanate or toluene-2,6-diisocyanate, preferably dimethylbiphenyl diisocyanate; the polyol is polybutadiene glycol, polybutylene adipate (diol), polybutylene glycol, polycaprolactone (diol), polyethylene adipate (adipate) propylene glycol (adipate) ester (diol), polytetramethylene glycol, polyoxytetramethylene glycol, polytetrahydrofuran, polytetramethylene ether glycol, polypropylene glycol or polyoxypropylene glycol, preferably polybutylene adipate (diol); the solvent is ethyl acetate, dioxane, benzene, toluene, xylene or dimethylformamide, preferably dioxane; the chain extender is 1,4-butanediol, ethylene glycol, diethylene glycol, neopentyl glycol , glycerol, trimethylolpropane, 3,3'-dichloro-4,4'-diaminodiphenylmethane, 3,5-dimethylthiotoluenediamine, 3,5-diethyltoluenediamine, 2,4-diamino-3,5-dimethylthiochlorobenzene, isophoronediamine, ethanolamine, diethanolamine, triethanolamine or triisopropanolamine, N,N-bis(2-hydroxypropyl)aniline, preferably 1,4-butanediol; the catalyst 1 is dibutyltin dilaurate, phenylmercuric acetate, phenylmercuric propionate, stannous octoate, potassium isooctanoate, potassium acetate, di(dodecylsulfide)dibutyltin, tetramethylethylenediamine, tetramethylpropylenediamine, N-methylimidazole, N-methylmorpholine or 1,4-dimethylpiperazine, preferably dibutyltin dilaurate; the activator is thionyl chloride , oxalyl chloride, phosphorus trichloride, phosphorus oxychloride, diketene, phthalic anhydride, p-toluenesulfonyl isocyanate, methacryloyl chloride, methacrylic anhydride, methacrylic acid, dicyclohexylcarbodiimide, N,N-diisopropylcarbodiimide, carbodiimide hydrochloride, 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate, O-benzotriazole-tetramethyluronium hexafluorophosphate or O-benzotriazole-N,N,N',N'-tetramethyluronium tetrafluoroborate, preferably oxalyl chloride; the catalyst 2 is 4-dimethylaminopyridine, 4-pyrrolidinylpyridine, N-hydroxysuccinimide, 1-hydroxybenzotriazole or 1-hydroxy-7-azabenzotriazole, preferably 4-pyrrolidinylpyridine;The passivator is ethylenediamine, n-propylamine, 1,3-propylenediamine, n-butylamine, 1-aminopentane, 3-aminoethylbenzene, 1-phenylpropan-1-amine, 4-methylphenylethylamine, 3,3-diphenylpropylamine, 3-methyl-1-phenylethylbutylamine, m-methylphenylethylamine or 1-naphthylmethylamine, preferably 4-methylphenylethylamine; the reaction materials of polyisocyanate, polyol, solvent, chain extender, catalyst 1, ore base material 2, activator, catalyst 2 and passivator are 0.1 mol:0.08~0.25mol:15~500mL:0.1~12.8mmol:0.01~0.93mg:3~15g:0.07~0.14mol:0.2~15mg:0.04~0.50mol, preferably 0.1mol:0.17mol:320mL:11.2mmol:0.66mg:8g:0.12mol:10mg:0.10mol. ; 2. The method for preparing the antique pigment according to claim 1, characterized in that: In step (1), the ore raw material is crushed after initial screening, a soluble alkaline salt is added, stirred evenly and piled in an open-air natural environment for 24 months; the ore raw material after piling is crushed and ground again and placed in an oriented magnetic field with a magnetic field strength of 455 mT to adsorb and remove impurities; the ore powder is washed with a dilute acid solution for 5 times, drained and washed with water to a pH of 6.8, and then prepared into a suspension with water, and centrifuged to separate the solid and liquid.

3. The method for preparing the antique pigment according to claim 1, characterized in that: In step (1), the ore is lapis lazuli, lapis lazuli, lapis lazuli, dianqingshi, malachite, cinnabar, vermilion, orpiment, realgar, orpiment, ochre, ochre, bean green, maleic acid, cerulean, azurite, cyan, green, sapphire, chalk or black ochre.

4. The method for preparing the antique pigment according to claim 1, characterized in that: In step (1), the soluble alkaline salt is sodium carbonate, potassium sulfite, sodium bicarbonate, potassium sulfate, sodium hypochlorite, sodium thiosulfate or trisodium phosphate, preferably sodium thiosulfate.

5. The method for preparing the antique pigment according to claim 1, characterized in that: In step (1), the dilute acid is 0.02-0.5 mmol / L hydrochloric acid, nitric acid or sulfuric acid, preferably 0.08 mmol / L hydrochloric acid.

6. The method for preparing the antique pigment according to claim 1, characterized in that: In step (1), the mixed acid is concentrated sulfuric acid, concentrated nitric acid, perchloric acid, concentrated hydrochloric acid, hydrobromic acid, hydroiodic acid, perbromic acid, hydroiodic acid, fluorosilicic acid, chlorolead acid, metaphosphoric acid, osmic acid, permanganic acid, selenic acid, ferric acid, fluoroboric acid, fluorosulfonic acid, cyanic acid, thiocyanic acid, 2,4,6-trinitrophenol, 2,4,6-trinitrobenzoic acid, trifluoroacetic acid, trichloroacetic acid, methanesulfonic acid, benzenesulfonic acid, KMD acid, oxalic acid, 2-chloroethanethiol, fluorine antimony A combination of two or more of sulfonic acid, perfluorosulfonic acid resin, carborane acid, and Trimble volatile acid in any ratio, preferably a combination of concentrated sulfuric acid and permanganic acid, with a mixing ratio of 5g:0.2g; the reaction material ratio of ore, soluble alkaline salt, water for preparing suspension, and mixed acid is 10.0g:0.5-2.3g:20-200mL:20-100mL, preferably 10.0g:0.7g:160mL:57mL.

7. The method for preparing the antique pigment according to claim 1, characterized in that: In step (2), the ore base material 1 is added to the connecting material and dispersed evenly, and then the colloid, honey, filler and rosin are added and dispersed evenly again, and then placed in a cool and dry environment for aging for 3 years, and the deteriorated areas are removed to obtain the product.

8. The method for preparing the antique pigment according to claim 1, characterized in that: In step (2), the colloid is animal colloid or plant colloid, wherein the animal colloid is tortoise shell glue, egg white, fish maw boiled extract, animal leather boiled extract or beeswax, and the plant colloid is agar, peach gum, sesbania gum, guar gum, sesame gum, fenugreek gum, eucommia gum or glutinous rice soup, preferably tortoise shell glue; the honey is rape honey, linden honey, vitex honey, loquat honey or sophora japonica honey, preferably linden honey; the filler is 80-2000 mesh calcium bicarbonate powder, titanium dioxide powder, white charcoal Black powder, alumina powder, montmorillonite powder, pearl powder or shell powder, preferably 800 mesh titanium dioxide powder; the rosin is horsetail rosin, wetland rosin, Simao rosin, longleaf rosin, Cuban rosin or torch rosin, etc., preferably Simao rosin; the mass ratio of the reaction materials of ore base material 1, connecting material, colloid, honey, filler and rosin is 80:5-18:2-10:0.01-0.50:2-10:0.2-0.9, preferably 80:13:8:0.41:4:0.

4.

9. The method for preparing the antique pigment according to claim 1, characterized in that: In step (2), the connecting material is prepared by: fully dissolving polyisocyanate and polyol with solvent, adding the mixture and heating to 182°C, adding chain extender, catalyst 1 and ore base material 2, and then keeping the temperature for 11 hours; adjusting the system temperature to 92°C, adding activator and catalyst 2, and keeping the temperature for 9 hours; adjusting the system temperature to 12°C, adding passivator, and keeping the temperature for 22 minutes; adjusting the system temperature to room temperature and removing most of the solvent to obtain ore base material grafted polyurethane, i.e., connecting material.

10. An antique pigment prepared according to any one of claims 1 to 9.